KESESUAIAN KONSUMSI PANGAN ANAK INDONESIA DENGAN PEDOMAN GIZI SEIMBANG - Hardiansyah, Angga; Hardinsyah, Hardinsyah; Sukandar, Dadang (Nutri-Sains: Jurnal Gizi, Pangan dan Aplikasinya, 2017)
Prevalence of malnutritions in childern still high in Indonesia. Bad food consumption is one of several causes of malnutritions. Therefore, food consumption of childern need to be analyzed The objective of this study were to analyze food consumption of childrens 2-12 years old and compare it with Balanced Nutrition Guidelines in Indonesia. This study design was cross-sectional. Subjects were 38890 childrens 2-12 years old of basic health survey of Ministry of Health. Food consumption data were collected by 24 hour recall method. Food consumption patterns presented in the participation and quantity, which devided in to 1) carbohydrate foods), 2) vegetables, 3)fruits, 4) animal foods (included milks), and 5) vegetable proteins. The participation of consumption of carbohydrate foods, vegetables, fruits, total animal foods, milks, and vegetable proteins were 99.9%, 57.6%, 14.0%, 80.0%, 20.4%, and 36.4% respectively. The quantity of consumption of carbohydrate foods, vegetables, fruits, total animal foods, milks, and vegetable proteins were 353.1 â 534.3 gram (3.5 â 5.5 portions), 44.4-72.6 gram (0.44 â 0.72 portions), 88-90 gram (2 portions), 28-244 ml (0.2-2 portions), and 17.6 â 32.6 gram (0.35 â 0.65 portions) recpectively. Subjects had high consumption of carbohydrate foods, but had low consumption of vegetables, fruits, total animal foods, milks, and vegetable proteins. In conclusion, food consumptions of subjects were not accordance with Balanced Nutrition Guidelines. Â